A bibliometric analysis based review on wind power price. (15th November 2016) - Gao, Cuixia; Sun, Mei; Geng, Yong; Wu, Rui; Chen, Wei
Highlights: In order to promote the application of wind power, appropriate wind power price should be regulated. A bibliometric analysis approach is employed to review the progress of wind power price. Research hotpots on wind power price were identified. Future research directions on wind power price were proposed. Abstract: With the increasing negative effects of fossil fuel combustion, many countries have paid more attention on supporting environmentally friendly energy generation, particularly renewable and sustainable energy sources (RES). However, renewables still cannot economically compete with fossil-fuels and are facing new challenges. Appropriate electricity pricing mechanism plays a vital role on mitigating the stress of limited fossil fuels and can promote renewable energy consumption. As one major type of renewable energy, wind power has been globally promoted. In order to promote the application of wind power, appropriate wind power prices (WPP) should be established by considering the local conditions. This paper targets such a field and conducts a bibliometric and network analysis based on the data from Scopus. The results show that the numbers of total related publications are gradually increasing, with the US as the leading country. European countries also have outstanding achievements. Moreover, both the most cited articles and keywords distribution offer future research directions. In general, this study provides valuable insights to both wind power researchers and practitioners.